The new chain gang: Corrections in the next century - Allen, Harry E. (American journal of criminal justice, 1997)
This article examines the operations and excesses of the correctional chain gang as a group of prisoners working outside a penal facility under armed correctional supervision and wearing chains or other restraining devices to prevent escape. We detail the operations and excesses of earlier chain gangs, identifying variables that contributed to the contemporary phase that emerged in 1995. Predicated on vengeance, retributive justice, and punitiveness, the chain gang represents yet another devolving standard of human decency in correctional policies. Future scenarios are explored.